A comparison of ICG-NIR with blue dye and technetium for the detection of sentinel lymph nodes in vulvar cancer. Issue 2 (February 2023) - Rundle, Stuart; Korompelis, Porfyrios; Ralte, Angela; Bewick, Diane; Ratnavelu, Nithya
Abstract: Introduction: The sentinel lymph node (SLN) procedure for vulva cancer is a safe alternative to a radical inguino-femoral lymphadenectomy (IFLN) for small unifocal tumours. SLN evaluation through biopsy and ultra-staging has helped gynaecological oncology surgeons improve operative morbidity with no cost to oncologic safety. Established techniques for groin SLN detection and excision in vulvar cancer use 99m Tc-nanocolloid radiotracer and blue dye (BD) for identification of the SLN. Indocyanine green (ICG)-near infrared (ICG-NIR) techniques for SLN mapping have proven utility in other gynaecological cancer sites and is gaining interest as a technique for SLN mapping in vulvar cancer Methods: Fifty consecutive patients with unifocal vulvar squamous cell cancers of <40 mm lateral diameter and with depth of invasion > 1 mm underwent SLN mapping and excision using a combination of 99m Tc-nanocolloid, BD and ICG. SLN detection results were recorded on a per-patient and per-groin basis. The success rates SLN for detection by individual tracer substance or combinations of tracer were determined by presence of one or more tracer, detectable in the SLN specimen. Results: 92% of patients had a successful SLN procedure. The per-groin detection rate was 84%. All successfully mapped SLN were identified with the combination of ICG-NIR and 99m Tc-nanocolloid compared to 69% with BD 99m Tc-nanocolloid. Success rates for the SLN procedure were not dependent on prior excision of the primary lesion or operator experience. Conclusions: Incorporation of ICG-NIR into standard SLN mapping protocols may allow for the abandonment of routine use of BD and its poor side effect profile. Highlights: Indocyanine green near infra-red (ICG-NIR) fluorescence is an effective adjunct to 99m Tc for the intra-operative detection of sentinel lymph nodes (SLN) in early stage vulvar cancer. ICG-NIR out-performed Blue-Dye (BD) in combination with 99m Tc for SLN detection. Incorporation of ICG-NIR into standard SLN mapping protocols may allow for the abandonment of routine use of BD.